2022
DOI: 10.1002/lary.30030
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Treatment Differences Between T1a and T1b Glottic Cancer

Abstract: Objectives This study was designed to evaluate significant differences in treatment and survival outcomes between patients with T1a and T1b glottic cancer. Methods Patients within the SEER Research Plus, 18 Registries dataset who were diagnosed with Stage I T1a or T1b cancer of the glottis between 2004 and 2015 were included in this study. Data prior to 2004 could not be included, as the SEER database did not distinguish between T1a and T1b glottic cancer until that year. Results The 5‐year disease‐specific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, there was no significant difference between the two groups regarding the number of days until recurrence (P = .27). Early glottic carcinoma recurrence has been linked to anterior commissure involvement [34][35][36][37] ; however, Ahmed et al found no significant increase in recurrence risk in either group with anterior commissure involvement. 33 In the study by Strieth and colleagues, the recurrence rate in KTP compared to CO 2 was 0% versus 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was no significant difference between the two groups regarding the number of days until recurrence (P = .27). Early glottic carcinoma recurrence has been linked to anterior commissure involvement [34][35][36][37] ; however, Ahmed et al found no significant increase in recurrence risk in either group with anterior commissure involvement. 33 In the study by Strieth and colleagues, the recurrence rate in KTP compared to CO 2 was 0% versus 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%